A Most Uncertain Crusade : The United States, the United Nations, and Human Rights, 1941-1953 - Brucken, Rowland (Book collections on Project MUSE., 2013)
"Traces the emergence of human rihgts as both an accepted international concern and as a controversial domestic issue for American policymakers during and after World War II. Brucken explains why the U.S. government, after issuing wartime declarations that called for the definition and enforcement of international human rights standards, subsequently refused to ratify the first U.N. treaties that fulfilled those twin purposes"--